CHARACTERISTICS OF FARMING AND TREKKING TOUR PACKAGES IN NORTH BALI - Putu Eka Wirawan (Institut Pariwisata dan Bisnis Internasional, 2016)
Buleleng regency in North Bali is one of the districts that tourism in the area has not developed optimally. Topography of southern part in Buleleng regency in the form of plateau has the potential to develop rural tourism. Munduk village in Banjar subdistrict is one of the village that have potential to be developed as rural tourism because it is located away from the bustle of the city and the societal conditions tends to traditional. Munduk village started to move forward to welcome the arrival of tourism. This study uses the concept of the cycle of attraction and stage the level of relationship between tourists and local people or local society. Bali Lofty Tours and Travel is a company which concerned about the education of tourism in Bali, as evidenced by the provision of education programs or education tour. Trekking activities'in Munduk village involve the local people who tend to remain in the stage of euphoria. People welcome the presence of tourists. In addition, Munduk village has arrived in stages between involvement and development. The purpose of this study was to provide knowledge and a general description of trekking in the Munduk village and its relation to rural tourism. Data were collected using observational and in-depth interviews methods, also by using sampling purposes method, the data analytic method using qualitative descriptive.By writing this paper expected that the promotion is not only done at schools outside of Bali, but also schools in Bali and by increasing activity in farming package in Munduk village and the government should assist in the promotion, improve road access and also supply parking area in Munduk village.